Rumen Ciliate Fauna of Domestic Sheep in Kastamonu, Turkey, and Infraciliature of Diplodinium quinquespinosum, Metadinium affine, and M. tauricum (Entodiniomorphida, Ophryoscolecidae) - Berber, Belma; Gürelli, Gözde (Magnolia Press, 2019)
Species distribution and composition of the ciliates found in the ruminal contents of 15 domestic sheep (Ovis aries) living in Kastamonu, Turkey, were investigated. Twenty-four species and 8 morphotypes belonging to 10 genera were identified. The density of the rumen ciliates in sheep was 108.2 (± 150.8) × 104 cells ml−1, and the mean number of ciliate species per host was 10.7 ± 4.6. Among the ciliate species identified, Dasytricha ruminantium was the most abundant, with a prevalence of 93.3%, whereas Diplodinium quinquespinosum, Eudiplodinium rostratum, and Metadinium tauricum were detected in only one animal (6.7% prevalence). D. quinquespinosum, Eudiplodinium rostratum, and Entodinium simulans m. dubardi were detected for the first time in sheep from Turkey. This is the first report of the presence of D. quinquespinosum in the rumen of ruminants in Turkey. The infraciliature of D. quinquespinosum, Metadinium affine, and M. tauricum (Entodiniomorphida, Ophryoscolecidae) was investigated. D. quinquespinosum and M. affine had Diplodinium-type infraciliature, whereas M. tauricum possessed Metadinium medium-type infraciliature.
Keywords: Rumen; Sheep; Turkey; Animals; Ciliophora